Apicoectomy and retrograde filling as periapical granuloma treatment: a case report - Daniela Villarreal-Arango; Jacobo Ramos-Manotas; Antonio José Díaz-Caballero (Universidad de Antioquia, 2016)
Periapical granulomas are chronic inflammatory processes appearing as a lesion around the apex of the tooth, which increase in size due to a proliferation of granulomatous tissue formed by lymphocytes, plasmocytes, some polymorphonuclears, macrophages, eosinophils, multinucleated giant cells, fibroblasts, and neoformation of capillaries. Etiologically, they occur due to deep caries affecting the pulp, infected root canals or endodontic failures. The objective of the present article is to report the finding of a periapical granuloma in a previously treated tooth, by means of excisional biopsy, curettage, and apical surgery with retrograde filling using mineral trioxide aggregate (MTA) as filling material on tooth # 11 in a 65-year old male patient, with subsequent histopathological study of the lesion. The clinical and radiographic follow-up showed the effectiveness of MTA as a retrograde filling material and apicoectomy as surgical procedure for the treatment of periapical granuloma.